2014
DOI: 10.1038/tpj.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of a patient with early-stage small-cell lung cancer

Abstract: We performed whole-genome sequencing (WGS) of a case of early-stage small-cell lung cancer (SCLC) to analyze the genomic features. WGS revealed a lot of single-nucleotide variations (SNVs), small insertion/deletions and chromosomal abnormality. Chromosomes 4p, 5q, 13q, 15q, 17p and 22q contained many block deletions. Especially, copy loss was observed in tumor suppressor genes RB1 and TP53, and copy gain in oncogene hTERT. Somatic mutations were found in TP53 and CREBBP. Novel nonsynonymous (ns) SNVs in C6ORF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…There was no difference in protein‐altering SNV and mutation rate between NAC and CTN group. In the present study, in addition to the recurrent deletion of regions harboring FHIT and RB1 , amplifications of MYCL1 and SOX2 were confirmed 33,34 . Xiaohui Ni et al confirmed that circulating tumor cells (CTCs) from an individual patient exhibited reproducible CNV patterns, 35 and CNV patterns remained constant during treatment.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…There was no difference in protein‐altering SNV and mutation rate between NAC and CTN group. In the present study, in addition to the recurrent deletion of regions harboring FHIT and RB1 , amplifications of MYCL1 and SOX2 were confirmed 33,34 . Xiaohui Ni et al confirmed that circulating tumor cells (CTCs) from an individual patient exhibited reproducible CNV patterns, 35 and CNV patterns remained constant during treatment.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, in addition to the recurrent deletion of regions harboring FHIT and RB1 , amplifications of MYCL1 and SOX2 were confirmed. 33 , 34 Xiaohui Ni et al confirmed that circulating tumor cells (CTCs) from an individual patient exhibited reproducible CNV patterns, 35 and CNV patterns remained constant during treatment. Different from the study by Xiaohui Ni, NAC group demonstrated more deletions than CTN group, especially on 5q31.3 and 17p13.1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the sequencing technology advances and the costs fall down, whole-genome sequencing (WGS) is turning to be a cost-effective way to obtain the comprehensive genetic information for tumors and other human complex genetic diseases [1822]. A list of LUAD related somatic alterations have been identified through WGS and other high-throughput studies [4, 2325].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the TNM staging in this study utilized the sixth edition, rather than the currently used eighth edition TNM staging guildelines. Additionally, SCLC has a unique genome map, as demonstrated by next generation sequencing, and parameters such as gene mutation may be used to predict survival in future studies.…”
Section: Discussionmentioning
confidence: 99%